Demographic Factors and Truancy Behaviour among Secondary School Students in Ilorin Metropolis, Kwara State - Elizabeth Ronke Ehindero; Adekola Kamil Lasisi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Contemporary secondary school students exhibit a wide range of social maladjustment behaviours, especially truancy. Given this, the present study looked into the Demographic Factors Influencing Truancy Behaviour among Secondary School Students in Ilorin Metropolis, Kwara State. Method: The study used descriptive survey design with a multi-stage sampling procedure which involved purposive, stratified, and simple random methods. The research involved a total of 400 participants. The